Mathematical Model of Improved Reverse Charging of Wireless Internet Pricing Scheme in Servicing Multiple QoS - F M Puspita; D R Nur; A L Tanjung; J Silaen; W Herlina; Yunita Yunita (Journal of Engineering and Scientific Research, 2019)
This paper seeks to utilize the improved model of reverse charging scheme. Reverse charging basically is defined as a capability of stored network that replaces the network used when the network is suddenly shut down. In this paper, charging back on 3G and 4G network that is user automated platform, will change the access of 4G to 3G and on the contrary when platform conduct thehosting. This research was solved as a problem Mixed Integer Nonlinear Programming (MINLP) by LINGO 13.0. An optimal pricing scheme is applied to a local data server, including digilib traffic and mail traffic. The improved model of Reverse Charging is modified into 4 cases and formed by setting the base price (?) and service level (?). Based on the analysis that has been done, the results of this study indicate that the reverse charging model can be utilized Internet Service Provider (ISP) to maximize profits and provide quality services for the user if compared to previous model without reverse charging scheme